Ergo design in Project Management Based on the General Theory of Transport Systems in the Conditions of the 10th Technological Order - Glushchenko, Valery Vladimirovich (ASEAN Journal of Science and Engineering, 2023)
The purpose of this study is to forecast the development of a project approach to the modernization of transport systems during the 10th technological order; descriptions of methodological provisions of the general theory of transport systems (transport ology, transport business theory). Studies of factors of growth of economic efficiency of project management in the field of transport formed by transport ology. Description of the algorithm for the implementation of ergo design policy in project management, formation of a factor model of increasing the economic efficiency of scientific support for project management in the modernization of transport systems. The methods of the article are ergo design, methodology of science, theory of technological orders, modeling, project approach, and analysis in project management. the scientific novelty of the article is connected with the formation of ergo design and the scientific theory of transport systems (transport ology, transport business theory) as a scientific basis for project management in the modernization of transport systems in the period of the 10th technological order.